Challenging al-Dhahabi's (1915-1977) Authority in the Historiography of Tafsir: A Clarification of His SalafÄ« Outlook - Qadafy, Mu'ammar Zayn (Universitas Islam Internasional Indonesia, 2022)
Recent discussions of modern historiographies of tafsīr show that al-Dhahabī’s al-Tafsīr wa al-Mufassirūn used the radical hermeneutic of Ibn Taymiyyah (d. 728/1328) as a philosophical underpinning, leading his book to present a somewhat salafī-history of the genre. This approach affirmed that the Qurʾān was repositioned squarely where the hermeneutical tools were unequivocally restricted to a hadith-inherited mode. A more holistic study on al-Dhahabī‘s scholarship, however, has yet to be undertaken. This article seeks to complete (and to some extent clarify) the image of al-Dhahabī's salafī leanings by situating his scholarship in the battlefield of ideas in Egypt from the 1940s to 1970s and undertaking a close reading of his other major books of tafsīr, including (1) al-Waḥy wa al-Qurʾān al-Karīm, (2) al-Isrāʾīlīyat fī al-Tafsīr wa al-Ḥadīth, (3) al-Ittijāhāt al-Munḥarifah fī al-Tafsīr, (4) al-Tafsīr wa al-Mufassirūn, and (5) Tafsīr Ibn ʿArabī. This article outlines Dhahabī’s systematic approach to the historiography of tafsīr. While his first three books provide theoretical considerations of what constitutes a good Qurʾānic commentary, the remaining two works are where he applies these theories into concrete judgements and classifications of tafsīr works. Besides the fact that Dhahabī has revitalized the problematic division of Tafsīr bi al-Maʾthūr and Bi al-Ra’y, several new key arguments highlighting his salafī outlook are identified throughout his books, namely his reinforcement of the value of the isnād system and his blatant attacks on commentaries that are not based on inherited interpretive materials. By shedding light on Dhahabī’s salafī orientation, this article argues for the need for alternative sources of the historiography of tafsīr to be studied in Indonesian Islamic Universities.